PENGARUH KOMPENSASI, STRES KERJA, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT BANK RAKYAT INDONESIA CABANG PUWOKERTO - Lynawati, Lynawati (Media Ekonomi, 2016)
This research aimed to know the influence of compensation, work stress, and communication towards employees performance and which variable among compensation, work stress, and communication have biggest influence towards employees performance. The hypothesis proposed is : 1) Compensation, work stress, and communication have significant influence towards employees performance of BRI Purwokerto Branch. 2) Compensation has biggest influence towards employees performance of BRI Purwokerto Branch compared by work stress and communication. This research was conducted at BRI Purwokerto Branch with the target is employees at its bank. Research method used survey. Data collecting method used questionnare, observation and documentation. Sampling technique used total sampling. Data analyzed method used path analysis. The first hypothesis test used F-test and t-test, while second hypothesis test used proportionate influence. Results of research showed that compensation, work stress, and communication both of partially and simultantly, have significant influence towards employees performance. It was proved by value of F-test and t-test bigger than F-table and t-table in level of significance 95%. Based from the result, so the first hypothesis was accepted. Compensation have biggest influence towards employees performance compared by work stress and communication. It was proved by value of proportionate influence is on variable of compensation. Based from that result, so the second hypothesis was accepted. Keywords: Compensation, Work stress, Communication, Performance